POLICY OF FOREIGN ECONOMIC COOPERATION OF THE GOVERNMENT OF THE REPUBLIC OF KOREA WITH ASEAN - Dok Hee OH; Kyung Sook GIL (Eastern European Journal of Regional Studies, 2024)
The Republic of Korea has achieved economic growth and development thanks to the benefits of trade liberalization within the framework of a multilateral trading system. However, it faced a new international trading environment with the emergence of neoprotectionism. Initially, neoprotectionism was promoted by developed countries, but now it is becoming a common phenomenon in the international trading environment. In particular, the political and economic conflicts between the United States and China are forcing a radical change in the foreign trade policy of the Republic of Korea. The prolonged confrontation between the two largest markets for the South Korean economy has reinforced the need to review the foreign economic policy of the Government of the Republic of Korea. In response to changes in the international trading environment, the Government of the Republic of Korea was forced to develop and promote new directions of foreign economic policy for the development of the multilateral trading system.